The association between markers of type I collagen synthesis and echocardiographic response to spironolactone in patients at risk of heart failure: findings from the HOMAGE trial. (5th July 2022) - Kobayashi, Masatake; Girerd, Nicolas; Ferreira, João Pedro; Kevin, Duarte; Huttin, Olivier; González, Arantxa; Bozec, Erwan; Clark, Andrew L.; Cosmi, Franco; Cuthbert, Joe; Diez, Javier; Edelmann, Frank; et al.
Abstract: Aims: Procollagen type I C‐terminal propeptide (PICP) and procollagen type III N‐terminal propeptide (PIIINP) are markers reflecting collagen synthesis in cardiac fibrosis. However, they may be influenced by the presence of non‐cardiac comorbidities (e.g. ageing, obesity, renal impairment). Understanding the associations between markers of collagen synthesis and abnormalities of cardiac structure and function is important to screen for myocardial fibrosis and monitor the antifibrotic effect of medications. Methods and results: The HOMAGE (Heart 'OMics' in AGEing) trial showed that spironolactone decreased serum PICP concentrations and improved cardiac remodelling over 9 months in a population at risk of developing heart failure (HF). We evaluated the associations between echocardiographic variables, PICP, PIIINP and galectin‐3 at baseline and during the course of the trial. Among 527 individuals (74 ± 7 years, 26% women), median serum concentrations of PICP, PIIINP and galectin‐3 were 80.6 μg/L (65.1–97.0), 3.9 μg/L (3.1–5.0), and 16.1 μg/L (13.5–19.7), respectively. After adjustment for potential confounders, higher serum PICP was significantly associated with left ventricular hypertrophy, left atrial enlargement, and greater ventricular stiffness (all p  < 0.05), whereas serum PIIINP and galectin‐3 were not (all p  > 0.05). In patients treated with spironolactone, a reduction in serum PICP during the trial was associated with a decrease in E/e′ (adjusted‐beta = 0.93, 95% confidence interval 0.14–1.73; p = 0.022). Conclusions: In individuals at high risk of developing HF, serum PICP was associated with cardiac structural and functional abnormalities, and a decrease in PICP with spironolactone was correlated with improved diastolic dysfunction as assessed by E/e′. In contrast, no such associations were present for serum PIIINP and galectin‐3. Abstract : In a population at risk of HF, independent of clinical confounders, higher serum concentration of procollagen type I C‐terminal propeptide (PICP) was associated with the presence of left ventricular (LV) hypertrophy and diastolic functional abnormalities (specifically, with greater left atrial [LA] volume indexed for body surface area and lower e′). In contrast, serum concentrations of procollagen type III N‐terminal propeptide (PIIINP) and galectin‐3 were not associated with abnormalities in any of the measures of cardiac structure or function. Additionally, in individuals treated with spironolactone, a decrease in serum PICP during a 9‐month period paralleled a decrease in E/e′.